TRANSFORMATIONAL LEADERSHIP OF SCHOOL PRINCIPALS IN THE IMPLEMENTATION OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN AN EFFORT TO IMPROVE ADMINISTRATIVE PERFORMANCE - Lina Herlina; Siti Pupu Fauziah; Muhammad Nurfadhilah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the principal's transformational leadership through the application of Organizational Citizenship Behavior (OCB) to improve the performance of administrative staff at Darma Bakti Junior High School, Baitul Mukaromah Foundation. The study employed a qualitative approach with a case study design. Data were collected through observation, semi-structured interviews, and documentation studies. Data were then analyzed using the interactive model of Miles, Huberman, and Saldana, with validity tested through triangulation of sources, methods, and theories. The results indicate that the principal's transformational leadership in developing OCB is manifested through three main strategies: exemplary leadership, continuous coaching and evaluation, and building a collaborative work culture. The implementation of these strategies encourages the development of three dimensions of OCB in administrative staff: altruism (voluntarily helping coworkers), conscientiousness (willingness to accept additional responsibilities), and civic virtue (active participation in organizational activities). The implementation of OCB has a positive impact on improving teamwork and cohesiveness, work effectiveness, and the quality of school administrative services. These findings indicate that the principal's transformational leadership plays an important role in building an organizational culture that supports improving the performance of administrative staff through the internalization of OCB values.